2020
DOI: 10.1136/bmjdrc-2019-001140
|View full text |Cite
|
Sign up to set email alerts
|

Shared genetic architecture and casual relationship between leptin levels and type 2 diabetes: large-scale cross-trait meta-analysis and Mendelian randomization analysis

Abstract: ObjectiveWe aimed to estimate genetic correlation, identify shared loci and test causality between leptin levels and type 2 diabetes (T2D).Research design and methodsOur study consists of three parts. First, we calculated the genetic correlation of leptin levels and T2D or glycemic traits by using linkage disequilibrium score regression analysis. Second, we conducted a large-scale genome-wide cross-trait meta-analysis using cross-phenotype association to identify shared loci between trait pairs that showed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 58 publications
4
11
0
Order By: Relevance
“…In relation to the metabolic syndrome, our results in the Dutch population are supported by two Mendelian randomization studies on leptin. One Mendelian randomization study showed a causal relation between leptin and HOMA-IR, which may explain the association between leptin and type 2 diabetes [47], whereas another Mendelian randomization study showed that leptin was also potentially causally associated with blood pressure, particularly among current smokers [48]. The findings of these two studies, which were conducted in a White/European descent majority population, support our observations of positive associations between leptin with hyperglycemia and hypertension in the Dutch population.…”
Section: Discussionsupporting
confidence: 76%
“…In relation to the metabolic syndrome, our results in the Dutch population are supported by two Mendelian randomization studies on leptin. One Mendelian randomization study showed a causal relation between leptin and HOMA-IR, which may explain the association between leptin and type 2 diabetes [47], whereas another Mendelian randomization study showed that leptin was also potentially causally associated with blood pressure, particularly among current smokers [48]. The findings of these two studies, which were conducted in a White/European descent majority population, support our observations of positive associations between leptin with hyperglycemia and hypertension in the Dutch population.…”
Section: Discussionsupporting
confidence: 76%
“…To identify the regions of shared loci more precisely, fine-mapping credible set analysis based on a Bayesian algorithm was performed to determine credible sets of causal variants at each of the shared loci (43)(44)(45). The identified credible sets of causal variants were 99% likely to contain causal disease-associated SNPs by extracting variants that were highly linked (r 2 > 0.4) with the index SNP and within 500 kb of the index SNP (46).…”
Section: Fine-mapping Credible Set Analysismentioning
confidence: 99%
“…Bidirectional MR is a form of causal inference analysis that can estimate causal directions and effects by employing genetic instruments selected from large-scale GWASs (55), even in the presence of unmeasured confounders. Three basic assumptions must be fulfilled to yield unbiased causal estimates in the MR analysis: 1) the genetic instruments used must be associated with the exposure, 2) the genetic instruments should be independent of the confounders between the exposure and outcome, and 3) the genetic instruments affect the outcome only through the exposure (46,56). In this study, we extracted genetic instruments (SNPs) with p < 5 × 10 −8 from the GWAS summary statistics of the exposure of interest, conducted the horizontal pleiotropy test, and selected independent genetic instruments at r 2 < 0.001 to satisfy these three assumptions.…”
Section: Bidirectional Mendelian Randomization Analysismentioning
confidence: 99%
“…The last two decades have witnessed great strides in GWASs ( Visscher et al, 2017 ), particularly increased samples and augmented power, and numerous single-nucleotide polymorphisms (SNPs) have been identified for common disorders, including self-reported back pain ( Freidin et al, 2019 ) and chronic back pain ( Suri et al, 2018 ). From the perspective of human genomics and genetic epidemiology, cutting-edge statistical tools such as linkage disequilibrium score regression (LDSC) ( Bulik-Sullivan et al, 2015 ; Zheng et al, 2017 ) and Mendelian randomization (MR) ( Hemani et al, 2018 ; Walker et al, 2019 ), have made it possible to use GWAS summary-level data to explore genetic correlation ( Wang et al, 2020 ; Zhuang et al, 2021 ) and make causal inference ( He et al, 2020 ; Zhang et al, 2020 ) within a wide spectrum of complex traits.…”
Section: Introductionmentioning
confidence: 99%